An Assessment of Menstrual and Genital Hygiene Behaviours among Adolescent Females at Gazimagusa, Northern Cyprus - Mamuk, Rojjin; Parlan, Hasret; Asif, Eren; Deveci, Muruvvet; Akdeniz, Ebru (Marmara Univ, Inst Health Sciences, 2022)
Objective: Inadequate menstrual and genital hygiene behaviours are common and important problems for adolescent health. This study aims to determine menstrual and genital hygiene behaviours and the affecting factors among female students enrolled in high schools located in Gazimagusa, Northern Cyprus. Methods: This school-based, cross-sectional, and descriptive study was conducted in three high schools in the Gazimagusa town borders in Northern Cyprus with 379 students. Data were collected through the Socio-demographic Form and the Genital Hygiene Behaviours Scale. Results: The scale mean score was found 79,28 +/- 6,80 (min:47 / max: 112). The factors affecting menstrual and genital hygiene behaviours were found to be the type of schools the students were enrolled (X2: 14,771 / P: 0,001), the education level of the mothers (X2: 9,806 / P: 0,020), and the education level of the fathers (X2: 15,879 / P:0,001). Conclusions: The participants of this study had an above-average level of right genital hygiene behaviours. Genital hygiene behaviours were found to be affected by the type of school, the education level of the mothers, and the education level of the fathers.
Keywords: Adolescents; behaviour; female; hygiene; menstruation